Modeling and simulation of the thermodynamics of lithium-ion battery intercalation materials in the open-source software Cantera. (10th November 2019) - Mayur, Manik; DeCaluwe, Steven C.; Kee, Benjamin L.; Bessler, Wolfgang G.
Abstract: Modeling and simulation play a key role in analyzing the complex electrochemical behavior of lithium-ion batteries. We present the development of a thermodynamic and kinetic modeling framework for intercalation electrochemistry within the open-source software Cantera. Instead of using equilibrium potentials and single-step Butler-Volmer kinetics, Cantera is based on molar thermodynamic data and mass-action kinetics, providing a physically-based and flexible means for complex reaction pathways. Herein, we introduce a new thermodynamic class for intercalation materials into the open-source software. We discuss the derivation of molar thermodynamic data from experimental half-cell potentials, and provide practical guidelines. We then demonstrate the new class using a single-particle model of a lithium cobalt oxide/graphite lithium-ion cell, implemented in MATLAB. With the present extensions, Cantera provides a platform for the lithium-ion battery modeling community both for consistent thermodynamic and kinetic models and for exchanging the required thermodynamic and kinetic parameters. We provide the full MATLAB code and parameter files as supplementary material to this article. Highlights: A thermodynamic model of intercalation materials is implemented in the open-source software Cantera. Fundamental thermodynamic models create a framework that enables flexible coupling of arbitrary combinations of materials. The code is demonstrated using a single-particle model of a graphite/LCO lithium-ion battery. The open-source nature of the software allows the exchange of parameters within the lithium-ion battery modeling community.